2013
DOI: 10.3109/00365599.2012.752403
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal exploration for acute scrotal pain: A 10-year experience in two tertiary referral paediatric units

Abstract: This study supports the practice of immediate surgical exploration with a clinical suspicion of testicular torsion in a paediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
(30 reference statements)
5
25
0
4
Order By: Relevance
“…Our study examined the current state of presentations in south‐eastern Victoria, and identified areas of delay in assessment and management of these patients. The majority of our patients had torsion of the testicular appendage, similar to the findings in the literature . These patients had a median age of 11.1 years, compared with 8.8–10 years reported in the literature .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our study examined the current state of presentations in south‐eastern Victoria, and identified areas of delay in assessment and management of these patients. The majority of our patients had torsion of the testicular appendage, similar to the findings in the literature . These patients had a median age of 11.1 years, compared with 8.8–10 years reported in the literature .…”
Section: Discussionsupporting
confidence: 86%
“…While the specific incidences of acute scrotal pain are not well documented, estimates of male genitourinary complaints range from 0.5% to 2.5% of all emergency department (ED) presentations . Within acute scrotal pain presentations, the incidences of testicular torsion are 9.2–46.5%, torsion of testicular appendage 22.8–68.3% and epididymo‐orchitis are 5.2–35% . Testicular torsion has been estimated to have an annual incidence of 1 in 4000 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These boys are less likely to have nausea and vomit than boys with testicular torsion. In approximately one third of patients, a nodule of the upper scrotum with bluish skin discoloration ("blue dot" sign) is palpated (18,19). This is a highly specific finding of this entity.…”
Section: Torsion Of the Testicular Appendagesmentioning
confidence: 99%
“…1 Although testicular appendage (TA) torsion is a more common cause of acute scrotal pain, 2-4 the risk of testicular ischaemia and subsequent tissue loss with missed testicular torsion has prompted many centres to advocate for early scrotal exploration in the management of the acute scrotum. 3,5,6 The aim of this study was to assess the frequency of representation to hospital in boys presenting with acute scrotal pathology, particularly regarding failed conservative management of TA torsion, presentation with pathology on the contralateral side to initial presentation, rates of testicular torsion following orchiopexy and post-operative complication rates following acute scrotal exploration. 3,5,6 The aim of this study was to assess the frequency of representation to hospital in boys presenting with acute scrotal pathology, particularly regarding failed conservative management of TA torsion, presentation with pathology on the contralateral side to initial presentation, rates of testicular torsion following orchiopexy and post-operative complication rates following acute scrotal exploration.…”
Section: Introductionmentioning
confidence: 99%